On Marxist Conception of Atheism - Jatkonis, Gintaras (Problemos, 1976)
The article discusses the concept “atheism” in several meanings: as a manifestation of the scientific world outlook, as a discipline, and a social phenomenon. All these three aspects of atheism may be objects of scientific investigation. The article also deals with some problems of the relationship between atheism and materialism; a tentative version of the structure and object of atheism as a science is presented.